Design and Manufacture of Speedometer Covers using the House of Quality (HOQ) Approach - Elka Faizal; Nurlia Pramita Sari; Hangga Wicaksono; Bayu Pranoto; Nicky Suwandhy Widhi Supriyanto; Subagiyo Subagiyo (G-Tech: Jurnal Teknologi Terapan, 2025)
This study aims to design and fabricate a speedometer cover for Yamaha Aerox and N-Max 155 motorcycles using 3D printing technology, guided by the House of Quality (HOQ) framework. The increasing consumer demand for motorcycle accessories motivated this research. A structured design process was implemented, beginning with a consumer needs analysis conducted through questionnaires and surveys to identify user expectations. These needs were systematically translated into technical requirements using the HOQ method. The design stage utilized 3D CAD modeling and 3D scanning to ensure accurate fitting to the speedometer unit, followed by prototyping using fused deposition modeling (FDM) 3D printing. The final prototype exhibited key consumer-desired attributes such as heat resistance, structural durability, and a secure fit. Results indicate that integrating the HOQ approach with digital fabrication methods effectively aligns product design with user expectations. This study demonstrates the potential for further development of customizable motorcycle accessories using a consumer-driven and technology-supported design process.